SUPPORTING LANGUAGE DEVELOPMENT IN MIXED-ABILITY CLASSROOMS - Rashidova Laziza Ilhomovna, (TADQIQOTLAR, 2026)
Abstract Supporting  language  development  in  mixed-ability  classrooms  is  a  critical challenge in contemporary English language teaching, where students differ widely in proficiency,  learning  styles, prior  knowledge, and  motivation. This  article explores strategies  to  enhance  language  acquisition  in  heterogeneous  settings  by  employing differentiated  instruction,  scaffolding,  collaborative  learning,  formative  assessment, and technology integration. Emphasis is placed on adapting content, process, product, and learning environment to student readiness, interests, and learning profiles. Practical approaches  for  vocabulary,  grammar,  reading,  writing,  speaking,  and  listening development  are  discussed,  alongside  methods  to  promote  learner  autonomy, engagement,  and  inclusive  participation.  The  article  highlights  the  importance  of culturally  responsive  materials,  ongoing  professional  development,  and  reflective teaching practices for sustaining effective language support. Ultimately, implementing these strategies fosters communicative competence, confidence, critical thinking, and lifelong learning skills among all learners in mixed-ability classrooms.